Prospective clinical trial of Intravitreal aflibercept treatment for PolypoIdal choroidal vasculopathy with hemorrhage or exudation (EPIC study): 6 month results. Issue 1 (December 2016) - Kokame, Gregg; Lai, James; Wee, Raymond; Yanagihara, Ryan; Shantha, Jessica; Ayabe, Julia; Hirai, Kelsi
Abstract Background Polypoidal choroidal vasculopathy is a variant of choroidal neovascularization and neovascular age related macular degeneration presenting with hemorrhagic and exudative changes within the macula and/or peripapillary region leading to vision loss. In contrast to neovascular age related macular degeneration, polypoidal choroidal vasculopathy has differing clinical manifestations and treatment strategies. Historically, polypoidal choroidal vasculopathy complexes are less responsive to anti-vascular endothelial growth factor therapy with no prospective clinical trials evaluating aflibercept in management of polypoidal choroidal vasculopathy. Herein we prospectively evaluate the efficacy and safety of intravitreal aflibercept in polypoidal choroidal vasculopathy. Methods A prospective, open-label, investigator-sponsored trial of intravitreal aflibercept for polypoidal choroidal vasculopathy in 21 eyes was conducted. Injections were administered monthly for 3 initial treatments, then every other month with monthly evaluations. The primary outcome measures were the mean change in best corrected visual acuity and adverse events. Secondary outcome measures included stabilization of vision, presence of subretinal hemorrhage, serous detachment, retinal pigment epithelial detachment, and regression of polypoidal complexes on indocyanine green angiography. Results At 6 months, the median visual acuity was 20/40 (range 20/25–20/200) with a mean Early Treatment Diabetic Retinopathy Study vision of 68.4 letters. There was a gain of 2.76 Early Treatment Diabetic Retinopathy Study letters at 6 months (p  = 0.15). No patient developed severe vision loss (≤15 letters) and vision was stable or improved in 19/21 eyes (91 %). Subretinal fluid resolved in 13/18 eyes (72 %), and subretinal hemorrhage resolved in 6/8 eyes (75 %) respectively. The polyps regressed in 14/21 eyes (67 %) and the branching vascular network decreased in 1 eye and was stable in all other eyes. The retinal pigment epithelial detachment improved in 13/15 eyes (87 %). Bimonthly treatment occurred in 15/21 patients (71 %). There were no adverse events. Conclusions Intravitreal aflibercept results in stabilization of vision, resolution of exudative and hemorrhagic complications with regression of polyps in polypoidal choroidal vasculopathy. Eyes with polypoidal choroidal vasculopathy previously treated with ranibizumab and bevacizumab can show marked improvement in the retinal pigment epithelial detachments and persistent polyps with aflibercept therapy. Trial registration Clinical trials.govNCT01871376, June 4th 2013